Peran Kompetensi Profesional Guru PAUD dalam Meningkatkan Kualitas Pembelajaran Berbasis Teknologi - Ayesha Nayra Edriano; Mutia Sandrina; Rifa Aska Auliya; Sherly Purnama Sari; Rita Kurnia; Asfi Yanti WE (MAN 4 Kota Pekanbaru, 2025)
This research aims to explain the role of the professional competence of PAUD teachers in improving the quality of technology-based learning. The focus of the study is directed to the teacher's ability to master teaching materials and integrate digital media in accordance with the child's development stage. The research uses a descriptive qualitative approach with the main data in the form of class observation results and interviews, involving three informants, namely class teachers, accompanying teachers, and the head of the institution. Data analysis is carried out through reduction techniques, presentation, and drawing conclusions. The findings show that teachers have mastered the material and are able to design relevant learning experiences, but the utilization of technology is still limited due to lack of technical skills and low confidence in operating digital devices. This research confirms the need for a continuous professional development (PKB) program that specifically strengthens the literacy and technology skills of PAUD teachers.